Modulating tumor reactive stroma by extracorporeal shock waves to control prostate cancer progression. Issue 13 (1st July 2020) - Rinella, Letizia; Pizzo, Benedetta; Frairia, Roberto; Delsedime, Luisa; Calleris, Giorgio; Gontero, Paolo; Zunino, Valentina; Fortunati, Nicoletta; Arvat, Emanuela; Catalano, Maria Graziella
Abstract: Background: Prostate cancer is the second most common cancer worldwide. Tumor microenvironment is composed of activated fibroblasts, the so called carcinoma‐associated fibroblasts (CAFs). They express high levels of α‐smooth muscle actin (α‐SMA) and type I collagen (COL1), and support proliferation and migration of tumor epithelial cells. Extracorporeal shock waves (ESWs), acoustic waves, are effective in the treatment of hypertrophic scars, due to their ability to modulate fibrosis. Based on this rationale, the study evaluated the effects of ESWs on CAF activation and the influence of ESW‐treated CAFs on the growth and migration of epithelial prostatic carcinoma cells. Methods: Primary cultures of CAFs (n = 10) were prepared from tumors of patients undergoing surgery for high‐risk prostate carcinoma. CAFs were treated with ESWs (energy levels: 0.32 mJ/mm 2, 1000 pulses; 0.59 mJ/mm 2, 250 pulses). After treatment, the messenger RNA and protein levels of the stromal activation markers α‐SMA and COL1 were determined. Subsequently, two different stabilized cell lines (PC3 and DU145) of androgen‐resistant prostate cancer were treated with the conditioned media produced by ESW‐treated CAFs. At different times, viability and migration of PC3 and DU145 cells were evaluated. Viability was also assessed by coculture system using CAFs and PC3 or DU145 cells. Results: ESWs reduced gene expression and protein level of α‐SMA and COL1 in CAFs. The treatment of PC3 and DU145 with conditioned media of ESW‐treated CAFs determined a reduction of their growth and invasive potential. Coculture systems between ESW‐treated CAFs and PC3 or DU145 cells confirmed the epithelial cell number reduction. Conclusions: This in vitro study demonstrates for the first time that ESWs are able to modulate the activation of prostate CAFs in favor of a less "reactive" stroma, with consequent slowing of the growth and migration of prostate cancer epithelial cells. However, only further studies to be performed in vivo will confirm the possibility of using this new therapy in patients with prostate cancer.